Nematode Hsp90: highly conserved but functionally diverse. Issue 9 (10th April 2014) - GILLAN, VICTORIA; DEVANEY, EILEEN
SUMMARY: Nematodes are amongst the most successful and abundant organisms on the planet with approximately 30 000 species described, although the actual number of species is estimated to be one million or more. Despite sharing a relatively simple and invariant body plan, there is considerable diversity within the phylum. Nematodes have evolved to colonize most ecological niches, and can be free-living or can parasitize plants or animals to the detriment of the host organism. In this review we consider the role of heat shock protein 90 (Hsp90) in the nematode life cycle. We describe studies on Hsp90 in the free-living nematode Caenorhabditis elegans and comparative work on the parasitic species Brugia pahangi, and consider whether a dependence upon Hsp90 can be exploited for the control of parasitic species.